Towards a better understanding of fashion clothing purchase involvement - Rahman, Mahfuzur; Albaity, Mohamed; Isa, Che Ruhana; Azma, Nurul (Emerald, 2018)
Purpose: This study aims to concern with Malaysian consumer involvement in fashion clothing. To achieve this, materialism, fashion clothing involvement and religiosity are examined as drivers of fashion clothing purchase involvement. Design/methodology/approach: Gender, race and age are explored to have better understanding of fashion clothing purchase involvement in Malaysia. Data were gathered using a Malaysian university student sample, resulting in 281 completed questionnaires. Findings: The results support the study’s model and its hypotheses and indicate that materialism, fashion clothing involvement and religiosity are significant drivers of fashion clothing purchase involvement. Also, materialism is a significant driver of fashion clothing involvement, and fashion clothing involvement mediates the relationship between materialism and fashion clothing purchase involvement. The results also show that Malaysian youth do not possess a high level of materialistic tendencies. Originality/value: This study offers enormous opportunities for the international apparel marketers to formulate relevant business policies and strategies.